Synthesis and Characterization of New Nanohybrids Based on Carboxymethyl Scleroglucan and Silica Nanoparticles - Rubén H. Castro; Laura M. Corredor; Isidro Burgos; Sebastián Llanos; Camilo A. Franco; Farid B. Cortés; Eduardo A. Idrobo; Arnold R. Romero Bohórquez (Nanomaterials, 2024)
In this study, two new nanohybrids (NH-A and NH-B) were synthesized through carbodiimide-assisted coupling. The reaction was performed between carboxymethyl-scleroglucans (CMS-A and CMS-B) with different degrees of substitution and commercial amino-functionalized silica nanoparticles using 4-(dimethylamino)-pyridine (DMAP) and N,N′-dicyclohexylcarbodiimide (DCC) as catalysts. The morphology and properties of the nanohybrids were investigated by using transmission (TEM) and scanning electron microscopy (SEM), electron-dispersive scanning (EDS), attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FT-IR), X-ray photoelectron spectroscopy (XPS), powder X-ray diffraction (XRD), inductively coupled plasma atomic emission spectroscopy (ICP-OES), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and dynamic light scattering (DLS). The nanohybrids exhibited differences in structure due to the incorporation of polyhedral oligomeric silsesquioxane (POSS) materials. The results reveal that hybrid nanomaterials exhibit similar thermal properties but differ in morphology, chemical structure, and crystallinity properties. Finally, a viscosity study was performed on the newly obtained nanohybrid materials; viscosities of nanohybrids increased significantly in comparison to the carboxymethyl-scleroglucans, with a viscosity difference of 7.2% for NH-A and up to 32.6% for NH-B.